The Growth of Caries in Primary Teeth and Some Correlations in a Longitudinal Study - Z. Broukal; R. Ivančaková; E. Lenčová (Czech Dental Chamber, 2009)
Caries experience dental status, oral hygiene and salivary levels of cariogenic streptococci were examined in the three years prospective study among older preschool children in relation to the dynamics of caries increment and with regard to the educational level of their mothers. Mean caries increment between the second and third year of study did not differ significantly amounting to 0.3 new decayed teeth per year however it was highest among children caries free in the onset of study. Higher caries experience significantly positively correlated with the presence of dental plaque and in the final of study also with the salivary levels of cariogenic streptococci. Mothers of caries free children assigned significantly higher educational level than those of children with tooth decay and on the contrary the proportion of children at need of restorative care was highest among mothers with elementary educational level. The educational level of mothers can be taken as the significant predictor of caries risk in children and as such it can be taken as one of important causes of the inequalities in oral health of children.